Cálculo de campos elétricos e magnéticos nas proximidades de linhas de transmissão: uma abordagem analítica e numérica - Pereira, Arthur Melo (2017)
In a society dependent on electric energy for the execution of various daily activities, it is normal that its use is increasingly increasing over time. In order to carry out the transportation of all electric energy, it is essential to use transmission lines, which with increasing energy demand inevitably have tended to multiply throughout the world, and especially in Brazil, given its continental dimensions. Considering the function of the transmission lines for the electrical system, its importance in the context of the electric power supply is remarkable. However, the lines constitute one of the great emitting sources of electric and magnetic fields of low frequency, which has caused concern and has been motivating fact of several studies, like the realized in this work. Therefore, in view of the scenario presented in the previous paragraph, it is necessary to establish ways of calculating the fields more and more precisely. For the calculation of the electric field is used the Image Method, the Maxwell Potential Coefficients Method and the Coulomb Law, and for the magnetic field the Biot-Savart's Law is used. The results obtained for the electric and magnetic fields were for infinite rectilinear geometries, finite rectilinear and for the conductors taking the form of a catenary, the latter geometry being the most real model for the arrangement of the conductors in a line. In all cases treated, an analytical and numerical approach was performed, in order to allow the calculation of the three geometries with accuracy. Taking advantage of the methodology of calculation of the fields, in addition this work proposes a method of support to the monitoring of transmission lines. The method consists of using the Genetic Algorithm associated to the values of the electric and magnetic fields measured to determine the parameters of the line, such as: phase spacing, cable-soil height, equivalent conductor diameter, current and operating voltage. Given the simplicity of implementation when compared to other methods, the achievement of satisfactory results and the need for a single measuring device to monitor the transmission line, the proposed method proves to be viable and promising to carry out the line monitoring process.